Immunomodulatory and Regenerative Effects of Mesenchymal Stem Cells and Extracellular Vesicles: Therapeutic Outlook for Inflammatory and Degenerative Diseases - Dabrowska, Sylwia; Andrzejewska, Anna; Janowski, Miroslaw; Lukomska, Barbara (Frontiers in Immunology, 2021)
Mesenchymal stem cells (MSCs) are non-hematopoietic, multipotent stem cells derived from mesoderm, which can be easily isolated from many sources such as bone marrow, umbilical cord or adipose tissue. MSCs provide support for hematopoietic stem cells and have an ability to differentiate into multiple cell lines. Moreover, they have proangiogenic, protective and immunomodulatory properties. MSCs have the capacity to modulate both innate and adaptive immune responses, which accompany many diseases, by inhibiting pro-inflammatory reactions and stimulating anti-inflammatory activity. Recent findings revealed that the positive effect of MSCs is at least partly associated with the production of extracellular vesicles (EVs). EVs are small membrane structures, containing proteins, lipids and nuclei acids, which take part in intra-cellular communication. Many studies indicate that EVs contain protective and pro-regenerative properties and can modulate an immune response that is activated in various diseases such as CNS diseases, myocardial infarction, liver injury, lung diseases, ulcerative colitis or kidney injury. Thus, EVs have similar functions as their cells of origin and since they do not carry the risk of cell transplantation, such as tumor formation or small vessel blockage, they can be considered a potential therapeutic tool for cell-free therapy.